THE UTILIZATION OF CORN COBÂ´S CRACKER AS ANTICIPATION OF HARVEST FAILURE FOR ECONOMIC IMPROVEMENT FOR FARMER IN NARIGUNUNG 1 VILLAGE, KARO REGENCY - Putra, Effendy De Lux; Yuliasmi, Sri; Prasetyo, Bayu Eko; Zebua, Nilsya Febrika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Narigunung 1 village is one of the villages located in Tiganderket District, Karo Regency, and North Sumatra Province. The community in this village consists of 150 heads of households whereby 90% earn a living by farming. The community manages various kinds of horticulture plants, especially vegetables and fruits, i.e. corn. The Geographic Village, which is located near to (Â± 8 km) the bottom of Sinabung mount, causes people often get crop failures, since the hot wind released from the Sinabung mount. Especially at the dry season, since the village is far from the source of water, therefore only relies on rain drops both for daily needs and for their agricultural lands. Failure of this harvest can reduce the economic welfare level of the community in the village. This community service activity was carried out, with the aim to stimulate the farmers and the community in Narigunung 1 village to make cracker businesses as a means of improving community welfare. The activity was carried out in the form of lectures, discussions, practice of making crackers from corn cobs, dissemination of food additives that were good for health, and the distribution of modules. After this service activity, the community in Narigunung 1 has been able to make crackers by utilizing corn cob which increases the economic value of the corn cob, using a grinding machine as a transfer knowledge of science and technology in the community and gain comprehensive knowledge about additional ingredients that are good for health.